Pathogen levels and clinical response to periodontal treatment in patients with Interleukin 8 haplotypes - Finoti, Livia S. [UNESP]; Corbi, Samia C. T. [UNESP]; Anovazzi, Giovana [UNESP]; Teixeira, Silvia R. L.; Capela, Marisa Veiga [UNESP]; Tanaka, Marcia H. [UNESP]; Kim, Yeon J. [UNESP]; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Mayer, Marcia P. A.; Scarel-Caminaga, Raquel M. [UNESP] (Wiley-Blackwell, 2013)
The aim of this study was to investigate the effect of non-surgical treatment of periodontitis on the levels of periodontopathogens and clinical parameters in patients with different genetic backgrounds produced by polymorphisms in the Interleukin (IL8) gene. Thirty patients grouped according to IL8 ATC/TTC or AGT/TTC haplotypes were submitted to non-surgical periodontal treatment. Levels of Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola were determined in 240 subgingival plaque samples by qPCR. The association between IL8 haplotypes and the levels of periodontopathogens and clinical parameters was investigated by multilevel analysis accounting for the clustering of diseased sites analyzed within patients. It was observed that neither levels of periodontopathogens nor non-surgical treatment was associated with the IL8 haplotype. The clinical parameters after periodontal treatment were similar in diseased and healthy sites, independently of the IL8 haplotype. Nonetheless, in the same period, diseased sites of AGT/TTC patients harbored higher levels of P. gingivalis, T. denticola, T. forsythia, and red complex than those of ATC/TTC patients. However, the non-surgical periodontal therapy decreased the levels of these periodontopathogens and of the tested clinical parameters of diseased sites in both groups. Non-surgical therapy is equally effective in improving clinical parameters and decreasing the levels of periodontopathogens, independent of the genotype groups produced by the IL8 haplotype.
Keywords: bacteria; chemokines; genetics; microbiology; periodontitis